Carbon credit card services and the impact potential on Co2 emissions in the Eu - market player analysis and measurement index assessment - Carrez, Nathalie Edmonde Anne (2022)
The study aims upon closer analysis to understand the emergence of two types of companies that have incorporated a carbon measurement service to individuals in their service offerings. Most attention centered to the European Union which proved to be more pertinent. Although similar in their objectives and positioning, differences were observed in firms’ respective business and revenue models, especially with regards to the possible adoption of a new payment card, the various approaches operated to assess individuals’ carbon footprint, and the ability to invest in emission reduction projects. Additionally, the potential of the CCCS market has been primarily emphasized given its potential global reach offering flexibility and scalability.